Effect of foliar spraying solution Grow green and Salicylic acid in growth of sour orange seedling ( Citrus aurantium L. ) - Saady Hasan, Jumhoriya (Journal of Kerbala for Agricultural Sciences, 2018)
This experiment was conducted in the Lathhous of the Technical Instituite Musaib during 2016 growth season on sour orange seedling, Which included two Factor : First was study the influence spraying (Grow green) in four levels (0 , 3 , 6 and 9) mg.L-1 and the second factor was study the effect of four levels of spraying with Salicylic acid (0, 50 , 100 and 150) mg.L-1 and their interaction on vegetative , root traits , leaves content of chlorophyll , Nitrogen , Phosphor and Potassium. The experiment in complete design of randomize (CRD) was done with three replicates and five Seedling for each treatment we have got the following results : Spraying solution (Grow green) at 9 mg.L-1 gave the highest means of all characters studied and the content of chlorophyll and (N , P , K) in the leaf. Spraying solution (Salicylic acid ) at 150 mg.L-1 caused highest mean of traits studied. Interaction between the treatment 9 mg.L-1 (Grow green ) Sapling with 150 mg.L-1 Salicylic acid gave the highest values of studied